Postoperative Hepatic Dysfunction After Frozen Elephant Trunk for Type A Aortic Dissection - Liang, Shenghua; Liu, Yanxiang; Zhang, Bowen; Dun, Yaojun; Guo, Hongwei; Qian, Xiangyang; Sun, Xiaogang (Frontiers in Cardiovascular Medicine, 2021)
Background: This study was aimed to investigate the incidence, risk factors, and outcomes of patients with postoperative hepatic dysfunction (PHD) after frozen elephant trunk (FET) for type A aortic dissection (TAAD). Method: A retrospective study was performed with 492 patients undergoing FET for TAAD between 2015 and 2019. Independent risk factors for PHD were determined by multivariate mix-effect logistic analysis with surgeon-specific factor as a random effect. Results: The incidence of PHD was 25.4% (n = 125) in our cohort. Patients with PHD presented higher early mortality (10.4% vs 1.1%, P < 0.001), rates of acute kidney injury (42.4% vs 12.8%, P < 0.001) and newly required dialysis (23.2% vs 3.0%, P < 0.001) compared with those without PHD. Moreover, with the median follow-up period of 41.3 months, the survival curve was worse in patients with PHD compared with no PHD group (log-rank P < 0.001), whereas was similar after excluding patients who died within 30 days (log-rank P = 0.761). Multivariable analyses suggested that PHD was predicted by preoperative aspartate transferase (Odd ratio [OR], 1.057; 95% confidence intervals [CI], 1.036-1.079; P < 0.001), celiac trunk malperfusion (OR, 3.121; 95% CI, 1.008-9.662; P = 0.048) and cardiopulmonary bypass time (OR, 1.014; 95% CI, 1.005-1.023; P = 0.003); retrograde perfusion (OR, 0.474; 95% CI, 0.268-0.837; P = 0.010) was associated with reduced risk of PHD. Celiac trunk malperfusion was an independent predictor for PHD but not associated with early mortality and midterm survival. Conclusions: PHD was associated with increased early mortality and morbidity, but not with late death in midterm survival. PHD was predicted by preoperative aspartate transferase, celiac trunk malperfusion, and CPB time and retrograde perfusion was associated with reduced risk of PHD.